One‐Pot Synthesis of Unprotected Anomeric Glycosyl Thiols in Water for Glycan Ligation Reactions with Highly Functionalized Sugars. Issue 50 (11th November 2016) - Köhling, Sebastian; Exner, Matthias P.; Nojoumi, Saba; Schiller, Jürgen; Budisa, Nediljko; Rademann, Jörg
Abstract: Chemical synthesis of oligosaccharide conjugates is essential for studying the functional relevance of carbohydrates, and this task would be facilitated considerably if reliable methods for the anomeric ligation of unprotected sugars in water were available. Here, a method for the preparation of anomeric glycosyl thiols from complex unprotected mono‐, di‐, and oligosaccharides is presented. By exploiting the neighboring‐group effect of the 2‐acetamido‐group, 1, 2‐oxazolines are generated and converted into 1‐glycosyl thioesters through treatment with 1‐thioacids. The unprotected anomeric glycosyl thiolates released in situ were conjugated to Michael acceptors, aliphatic halogenides, and aziridines to furnish versatile glycoconjugates. Conjugation of amino acids and proteins was accomplished using the thiol–ene reaction with terminal olefins. This method gives efficient access to anomeric glycosyl thiols and thiolates, which enables anomeric ligations of complex unprotected glycans in water. Abstract : Sweet dreams are made of these : A direct access to anomeric glycosyl thiols from unprotected mono‐ and oligosaccharides was developed. Sugar oxazolines were opened smoothly with thioacids to form odorless and storable glycosyl thioesters as precursors for 1‐thiol‐sugars, thiolates and, further functionalized glycosides, including those with amino and thiol spacers, S‐glycosidic amino acids, and S‐linked glycoproteins.